Metallic stents: Biomechanical analysis and in vivo investigation of the vessel inflammatory response - Kapnisis, Konstantinos; Pitsillides, Costas; Prokopi, Marianna; Constantinides, Georgios; Cristea, Daniel; Munteanu, Daniel; Brott, Brigitta C.; Anderson, Peter G.; Lemons, Jack; Anayiotos, Andreas (My University, 2016)
Despite a considerable clinical and investigative emphasis on the problem of in-stent restenosis (ISR), complications arising from the interaction of stent materials with the surrounding vessel wall as well as from the mechanical forces developing during and after implantation, remain a significant problem. Nanoindentation studies performed on various locations along the stent struts have shown that the hardness of specific stent locations significantly increases after mechanical expansion. The increase in hardness was associated with a reduction of the material‘s ability to dissipate energy in plastic deformations and therefore with an increased vulnerability to fracture and fatigue. It was concluded that the locations of fatigue fractures in stent struts are controlled not only by the geometrically-driven stress concentrations developing during cyclic loading but also by the local material mechanical changes that are imparted on various parts of the stent during the deployment process. Additionally, the project focused on investigating the effect of stent corrosion in an animal model in order to explore a possible link between metal ion release, inflammation and factors thought to initiate ISR. To evaluate the vessel inflammatory response, stents with active corrosion were implanted in mice abdominal aortas and novel in vivo imaging techniques were employed to assess the trafficking and accumulation of fluorescent donor monocytes as well as the proliferation of vascular smooth muscle cells at the implantation site. The in vivo imaging analysis revealed that elevated metal particle contamination, prompted by corroded stents, triggers an inflammatory response and promotes monocyte recruitment with upregulation of MMPs at the site of injury.
Keywords: Animal model; Biomechanical testing; In vivo imaging; In-stent restenosis; Stents